2021
DOI: 10.1016/j.bpj.2020.10.036
|View full text |Cite
|
Sign up to set email alerts
|

The flexibility of ACE2 in the context of SARS-CoV-2 infection

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has swept over the world in the past months, causing significant loss of life and consequences to human health. Although numerous drug and vaccine development efforts are underway, there are many outstanding questions on the mechanism of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) viral association to angiotensin-converting enzyme 2 (ACE2), its main host receptor, and host cell entry. Structural and biophysical studies indicate some degree of fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
120
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 84 publications
7
120
1
Order By: Relevance
“…Thus, it will be necessary to discuss not only one X-ray crystal structure but also other X-ray crystal structures and structural fluctuations by MD simulations. The flexibility of sugar chains on the SARS-CoV-2 S-protein and the ACE2 was already investigated by several MD simulations [22][23][24][25][26] . One of the results that the sugar chain on N90ACE2 works favorably for molecular recognition of the S-protein was reported as follows: The sugar chain on N90ACE2…”
Section: Sugar Chain Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it will be necessary to discuss not only one X-ray crystal structure but also other X-ray crystal structures and structural fluctuations by MD simulations. The flexibility of sugar chains on the SARS-CoV-2 S-protein and the ACE2 was already investigated by several MD simulations [22][23][24][25][26] . One of the results that the sugar chain on N90ACE2 works favorably for molecular recognition of the S-protein was reported as follows: The sugar chain on N90ACE2…”
Section: Sugar Chain Effectmentioning
confidence: 99%
“…conducted to better understand their association. [20][21][22][23][24][25][26] Approaches for drug/neutralizing antibody design targeting S-protein have been reported, such as a de novo design peptide inhibitors for SARS-CoV-2 27,28 , a virtual screening of antiviral compounds for the SARS-CoV-2 29 and sequence-based epitope analysis for the SARS-CoV-2, among others 30 . These previous studies have been based on the molecular recognition of S-protein and ACE2/antibody and were highly beneficial.…”
mentioning
confidence: 99%
“…Even less is known at the needed molecular level about the mechanism by which the FPs in the spearhead are involved in the fusion of the cell and virus membranes, despite the wealth of information that has recently accumulated from molecular dynamics (MD) simulations on SARS-CoV-2 models (e.g., see Refs. [24][25][26][27][28][29] ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yan et al [ 14 ] has published the structure of ACE2 in three conformations: an open conformation, a closed conformation, and a closed conformation in complex with a fragment of the viral S protein ( Figure 1 ). The ACE2 open and closed conformations differ from each other by the degree of opening of the catalytic site cleft of the peptidase domain ( Figure 1 b) [ 14 , 15 ]. This causes a distortion of the ACE2:S1 binding interface [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ACE2 open and closed conformations differ from each other by the degree of opening of the catalytic site cleft of the peptidase domain ( Figure 1 b) [ 14 , 15 ]. This causes a distortion of the ACE2:S1 binding interface [ 15 ]. Moreover, ligand binding studies have identified a closing motion associated with ligand binding, suggesting that the closed conformation represents the catalytically active state of the enzyme [ 16 ].…”
Section: Introductionmentioning
confidence: 99%